The determinants of financial inclusion - Naftaly Mose; John Thomi (Financial Internet Quarterly, 2021)
There are hosts of dynamics contributing to financial inclusion. These sources may be both from the demand side and supply side. The government and financial institutions use several policy initiatives to encourage the supply of financial services to the excluded sector. However, the demand-side factors of financial access have attracted little focus. This study provides an overview of sources of financial inclusion and highlights the policy measures from the perspective of consumers of financial services - also known as the demand-side. The secondary series data were estimated using the ordinary least square method. The findings of the study indicate that economic growth and the number of internet users exert a positive and significant effect on financial access in East Africa. On the other hand, the result indicates that the deposit interest rate was insignificant. The study recommends the deposit interest rate be made attractive to promote continuous saving and access to loanable funds in the financial market. The policy strategies therefore should be aimed at cultivating a conducive financial system that upholds financial access-demand-driven rates to stimulate financial growth.
Keywords: D14; E44; G28; 330; consumer finance; financial inclusion; financial institutions; macro economy